A Pseudo Freedom for Faith: A Discourse of Religious Freedom in Russia and Indonesia - Arvante, Jeremy Zefanya Yaka; Nugraha, Maulana Fuad; Arifin, Ridwan (Faculty of Law, Universitas Negeri Semarang, 2022)
This paper explores the complex landscape of religious freedom in Russia and Indonesia, despite constitutional guarantees in both nations. In Russia, historical legacies and state control have led to restrictions on religious pluralism, particularly affecting minority faiths and dissenting voices. The Orthodox Church's influence and government policies often contradict formal protections, creating a paradoxical environment. Similarly, in Indonesia, despite its religious diversity, state regulations, societal norms, and religious identity intersect to challenge genuine religious freedom. Discrimination and persecution against religious minorities persist amidst political interests and cultural tensions. This discourse analyzes the underlying factors contributing to this paradoxical situation, emphasizing historical contexts, political dynamics, and socio-cultural complexities. It underscores the need for nuanced approaches beyond legal frameworks to address deeper societal attitudes and power structures. By reflecting on these cases, this discourse prompts broader discussions on global religious freedom, advocating for genuine respect for religious diversity as a fundamental aspect of democracy and human rights. Understanding the complexities in Russia and Indonesia illuminates the challenges and opportunities for advancing religious freedom globally.